Risk factors of COVID-19 disease confirmed cases in Solok District - Nuraisyah, Fatma; Irjayanti, Apriyana; Irmanto, Maxsi; Fauziah, Khairani (International Journal of Public Health Science (IJPHS), 2024)
According to West Sumatra corona virus data, Solok Regency has the highest prevalence of positive confirmed cases of COVID-19 in West Sumatra, and one of the areas where the prevalence has increased significantly. Analysis of risk factors for COVID-19 cases in Solok Regency in 2021. We conducted a cross-sectional study analysis of secondary data from March to December 2020 with a mass randomized trial using the polymerase chain reaction (PCR) test in Solok Regency. Descriptive statistical analysis was used with secondary data relevant, and a logistic regression model was used to assess infection risk factors. A total of the 770 participants, 47.4% were women and 66% were aged 50-64 years. A total of 624 participants tested (81.03%) were identified as asymptomatic PCR SARS-CoV infection without symptoms, with 88% of participants with co-morbidities and 66% of participants without travel history. Based on the results obtained a significant relationship between history of comorbidities (p-value=0.00; AOR=0.16; 95% CI=0.08-0.32), clinical symptoms (p-value=0.00; AOR=0.04; 95% CI=0.03-0.08), and travel history (p-value=0.00, AOR=1.80, 95% CI=1.25-2.61). The majority of cases that were confirmed positive for COVID-19 based on the PCR test showed no symptoms, with co-morbidities and travel history. Confirmed positive cases of COVID-19 are associated with co-morbidities, symptoms and travel history.